Геноцид как Тяжкое Преступление (Genocide As Extraordinary Crime) - Nur Rohim Yunus; Latipah Nasution; Siti Nurhalimah; Siti Romlah (SALAM: Jurnal Sosial dan Budaya Syar-i, 2021)
The state is a subject of international law who has power or power, so that the state is required not to abuse its authority. State obligations have been regulated in various international legal instruments. The protection of human rights has implications for the emergence of the fulfillment of human rights as a form of state responsibility. The state in this case must ensure to protect, to ensure, and to fulfill the human rights. Therefore, all acts of the state that discriminate against citizens of a certain ethnicity by committing genocide are serious human rights crimes that must be prosecuted by the International Court of Justice. This study uses qualitative research with a sociological and juridical approach. The results of the study state that the State of Indonesia has also regulated the behavior of preventing the crime of genocide in order to protect human rights.Keywords: Genocide; HAM; Extraordinary Crime Abstrak:Negara merupakan subjek hukum internasional yang memiliki kekuasaan atau power, sehingga negara dituntut tidak melakukan penyalahgunaan wewenang. Kewajiban negara telah diatur dalam berbagai instrumen hukum internasional. Perlindungan terhadap HAM berimplikasi terhadap munculnya pemenuhan HAM sebagai wujud tanggungjawab negara. Negara dalam hal ini harus memastikan to protect, to ensure, and to fulfill the human rights. Oleh karenanya, segala tindakan negara yang melakukan diskriminasi kepada warga negara dari etnis tertentu dengan melakukan genosida merupakan kejahatan HAM berat yang harus dituntut oleh Mahkamah Internasional. Penelitian ini menggunakan penelitian kualitatif dengan pendekatan sosiologis dan yuridis. Hasil penelitian menyatakan bahwa Negara Indonesia juga telah mengatur perilaku pencegahan tindak kejahatan Genosida guna menjaga HAM.Kata Kunci: Genosida; HAM; Extraordinary Crime Аннотация:Государство является субъектом международного права, обладающим властью, поэтому от государства требуется не злоупотреблять своей властью. Обязательства государства регулируются различными международно-правовыми инструментами. Защита прав человека имеет значение для возникновения реализации прав человека как формы ответственности государства. Государство в этом случае должно гарантировать защиту, обеспечение и соблюдение прав человека. Следовательно, все действия государства, дискриминирующие граждан определенных этнических групп путем совершения геноцида, являются серьезными преступлениями в области прав человека, которые должны преследоваться Международным Судом. В данном исследовании используются качественные исследования с социологическим и юридическим подходом. Результаты исследования показывают, что государство Индонезия также регулирует действия по предотвращению преступления геноцида в целях защиты прав человека.Ключевые слова: геноцид; права человека; тяжкое преступление